Manilkzapotane, a novel dimeric alkylresorcinol derivative from the stem bark of Manilkara zapota. Issue 11 (15th November 2021) - Duong, Thuc-Huy; Trung, Nguyen Tien; Phan, Cam-Tu D.; Nguyen, Van-Kieu; Musa, Vassana; Ruksilp, Thanatip; Nguyen, Ngoc-Hong; Nguyen, Huu-Hung; Sichaem, Jirapast
Abstract: A novel dimeric alkylresorcinol derivative, manilkzapotane (1 ), along with seven known compounds, lupeol acetate (2 ), lupeol (3 ), arjunolic acid (4 ), ergosterol peroxide (5 ), taraxerol (6 ), hederagonic acid (7 ), and glochidiol (8 ) were isolated from the stem bark of Manilkara zapota . Their structures were determined on the basis of spectroscopic data. DFT-NMR chemical shift calculations and a modified probability (DP4+) method were applied to define the relative configuration of 1 . To the best of our knowledge, this represents the first isolation of a dimeric alkylresorcinol derivative from the Sapotaceae family. Graphical Abstract: UF0001